Surgical or percutaneous coronary revascularization for heart failure: an in silico model using routinely collected health data to emulate a clinical trial. (25th November 2022) - Pathak, Suraj; Lai, Florence Y; Miksza, Joanne; Petrie, Mark C; Roman, Marius; Murray, Sarah; Dearling, Jeremy; Perera, Divaka; Murphy, Gavin J
Abstract: Aims: The choice of revascularization with coronary artery bypass grafting (CABG) vs. percutaneous coronary intervention (PCI) in people with ischaemic left ventricular dysfunction is not guided by high-quality evidence. Methods and results: A trial of CABG vs. PCI in people with heart failure (HF) was modelled in silico using routinely collected healthcare data. The in silico trial cohort was selected by matching the target trial cohort, identified from Hospital Episode Statistics in England, with individual patient data from the Surgical Treatment for Ischemic Heart Failure (STICH) trial. Allocation to CABG vs. complex PCI demonstrated random variation across administrative regions in England and was a valid statistical instrument. The primary outcome was 5-year all-cause mortality or cardiovascular hospitalization. Instrumental variable analysis (IVA) was used for the primary analysis. Results were expressed as average treatment effects (ATEs) with 95% confidence intervals (CIs). The target population included 13 519 HF patients undergoing CABG or complex PCI between April 2009 and March 2015. After matching, the emulated trial cohort included 2046 patients. The unadjusted primary outcome rate was 51.1% in the CABG group and 70.0% in the PCI group. IVA of the emulated cohort showed that CABG was associated with a lower risk of the primary outcome (ATE −16.2%, 95% CI −20.6% to −11.8%), with comparable estimates in the unmatched target population (ATE −15.5%, 95% CI −17.5% to −13.5%). Conclusion: In people with HF, in silico modelling suggests that CABG is associated with fewer deaths or cardiovascular hospitalizations at 5 years vs. complex PCI. A pragmatic clinical trial is needed to test this hypothesis and this trial would be feasible. Structured Graphical Abstract: Structured Graphical Abstract In silico trial modelling, using variation in the regional rates of CABG vs. PCI as an instrumental variable, suggests that CABG is superior to PCI at 5 years for the primary composite outcome of all-cause-death or cardiovascular hospitalization. M, matched—emulated trial cohort; U, unmatched—targeted trial cohort; CABG, coronary artery bypass graft; PCI, percutaneous coronary intervention; CI, confidence interval.